Perspectives on Barriers to Eating Healthy Among Food Pantry Clients - Jayna M. Dave; Deborah I. Thompson; Ann Svendsen-Sanchez; Karen W. Cullen (Mary Ann Liebert, 2017)
Objective: To explore perspectives on barriers of eating healthy among food pantry clients. Methods: Food pantry clients participated in focus groups/interviews. Qualitative data were coded and analyzed using content analyses and grounded theory approach. Themes were then identified. Quantitative data were analyzed for frequencies and descriptives. Results: Fifty-four clients from 10 pantries participated in interviews/focus groups and completed questionnaires. Two major themes emerged: concern over obesity and other chronic diseases, and barriers to healthy eating. Several subthemes for barriers to healthy eating were identified: financial uncertainty, cost of healthy foods, lack of time, rationing food within family, lack of transportation, lack of adequate kitchen equipment, lack of nutrition knowledge and skills, and social support network. Conclusions: Issues identified above and those identified by others working with low-income populations need to be systematically addressed and incorporated into programs and nutrition education interventions for this group.